How Heavy Lifting Lightens Our Lives: Content Analysis of Perceived Outcomes of Masters Weightlifting - Huebner, Marianne; Arrow, Holly; Garinther, Alex; Meltzer, David E. (Frontiers in Sports and Active Living, 2022)
Although the benefits of sport participation for older adults has been well-documented, the traditionally masculine sport of weightlifting has only recently become popular among older women, who now participate at rates comparable to men in the United States. This study describes the self-reported effects of participating in Masters-level Olympic weightlifting on other aspects of life. Contrasting with previous studies of Masters athletes in other sports, the gender balance and broad age range of our sample allowed us to explore whether the self-reported impact of sport on older adults was similar or different across age groups (35–44, 45–59, 60, and older) for both men and women. A total of 352 (191 women, 159 men, 2 other) who completed a survey of Masters lifters registered with the United States national organization (USAW) responded to an open-ended question about how weightlifting has affected other aspects of their life. Across gender and age categories, responses indicated that weightlifting has a positive impact on physical health (strength, mobility, fitness) and on psychological (mental health benefits, stress reduction) and social aspects such as community connections. Female lifters mentioned psychological benefits such as increased confidence and help with stress and depression more commonly than male lifters; older lifters were more likely than middle-aged lifters to mention physical health benefits. Competition was a prominent theme across genders and age groups. The themes mentioned by participants are consistent with previous literature on sports that are less strongly gender-typed than weightlifting.